The acute effects of continuous positive airway pressure and oxygen administration on blood pressure during obstructive sleep apnea. - Ali, N; Davies, R; Fleetham, J; Stradling, J (1992)
We have measured blood pressure continuously with a digital artery blood pressure monitor in eight patients with severe obstructive sleep apnea (OSA) during 30 min each of wakefulness, OSA, OSA with added oxygen to keep saturation above 96 percent at all times (OSA+O2), and nasal continuous positive airway pressure (CPAP) therapy. Mean blood pressures were not different between wakefulness, OSA, OSA+O2, and CPAP, although the variability in blood pressure was significantly greater during OSA and OSA+O2 than during wakefulness and CPAP. The addition of oxygen did not attenuate the variability in blood pressure. Using multiple linear regression modeling to further dissect out the principal variables determining the postapneic blood pressure rise, we found that only apnea length (r2 = 0.28, p less than 0.0001) and pulse rate changes (r2 = 0.15, p less than 0.0001) remained significantly related to SBPmax, while hypoxemia did not. We found the same trends in the other variables SBPten, DBPmax, and DBPten. Hypoxemia made a small contribution to the size of DBPmax, although this was small by comparison with apnea length. We conclude that CPAP treatment of OSA does not lower mean blood pressure acutely, although it significantly reduces the large oscillations in blood pressure seen in patients with untreated OSA. The rise in blood pressure following each apnea is not primarily due to arterial desaturation but is related to apnea length and may be caused by increased sympathetic activity secondary to arousal.